Synthesis, density functional theory (DFT) studies and urease inhibition activity of chiral benzimidazoles. Issue 10 (October 2020) - Aman, Hasil; Rashid, Naghmana; Ashraf, Zaman; Bibi, Aamna; Chen, Hsin-Tsung; Sathishkumar, Nadaraj
Abstract: A variety of benzimidazole by the heterocyclization of orthophenylenediamine were synthesized in 69–86% yields. The synthesized compounds 3a-f and 6a-f were characterized and further investigated as jack bean urease inhibitors. Density functional theory (DFT) studies were performed utilizing the basis set B3LYP/6-31G (d, p) to acquire perception into their structural properties. Frontier molecular orbital (FMO) analysis of all compounds 3a–f and 6a-f was computed at the same level of theory to get a notion about their chemical reactivity and stability. The mapping of the molecular electrostatic potential (MEP) over the entire stabilized molecular geometry indicated the reactive centers. They exhibited urease inhibition activity with IC50 between 22 and 99 μM. Compounds containing withdrawing groups on the benzene ring (3d, 6d ) were not showing significant urease inhibition. The value obtained for 3a, 3b, 3f had shown their significant urease inhibition for both theoretical and experimental. Notably, the compound having S-configuration (3a ) (22.26 ± 6.2 μM) was good as compared to its R enantiomer 3f (31.42 ± 23.3 μM). Despite this, we elaborated the computational studies of the corresponding compounds, to highlight electronic effect which include HOMO, LUMO, Molecular electrostatic potential (MEP) and molecular docking. Abstract : Organic chemistry; Pharmaceutical chemistry; Theoretical chemistry, Benzimidazole; Urease inhibition; Density functional theory; HOMO; LUMO; Molecular docking